Alcohol-based Michaelis–Arbuzov reaction: an efficient and environmentally-benign method for C–P(O) bond formation. Issue 15 (7th June 2018) - Ma, Xiantao; Xu, Qing; Li, Huan; Su, Chenliang; Yu, Lei; Zhang, Xu; Cao, Hongen; Han, Li-Biao
Abstract : An n -Bu4 NI-catalyzed C–P(O) formation reaction of alcohols with phosphites, phosphonites, and phosphinites is developed for the synthesis of useful phosphoryl compounds. Abstract : The famous Michaelis–Arbuzov reaction is extensively used both in the laboratory and industry to manufacture tons of widely-used organophosphoryl compounds every year. However, this method and the modified Michaelis–Arbuzov reactions developed recently still have some limitations. We now report a new alcohol-version of the Michaelis–Arbuzov reaction that can provide an efficient and environmentally-benign method to address the problems of the known Michaelis–Arbuzov reactions. That is, a wide range of alcohols can readily react with phosphites, phosphonites, and phosphinites to give all the three kinds of phosphoryl compounds (phosphonates, phosphinates, and phosphine oxides) using an n -Bu4 NI-catalyzed efficient C–P(O) bond formation reaction. This general method can also be easily scaled up and used for further synthetic transformations in one pot.